FRIEDRICH LENGER, WERNER SOMBART 1863-1941 - Lane, Jan-Erik (Baltic Journal of Political Science, 2015)
The rise and roots of Nazi Germany is one of the most debated issues in social science today. It is a recurrent topic in the media and new books continue to provide further analyses and perspectives. The key question, of course, is how much did the Germans themselves know and approve of? Friedrich Lenger, a historian at the University of Giessen, gives a fascinating perspective on what has been called “the German catastrophe” with his penetrating study ofthe life and writings of Werner Sombart, the most quoted political and social scientist of the interwar years. [...]